Resident Education in Principles and Technique of Bowel Surgery Using an Ex-Vivo Porcine Model - M. Bijoy Thomas; V. Dandolu; P. Caputo; R. Milner; E. Hernandez (Obstetrics and Gynecology International)
Objective. improve competency of residents with lysis of adhesion (LOA) and bowel surgery using a porcine model. Study Design. Pig bowel was removed at time of an anatomy laboratory, cleansed, and used to demonstrate surgical techniques and principles of LOA, repair of enterotomy, bowel resection, and anastomosis. Participants were surveyed pre- and posttraining session using 10 point Likert scale. Results. Thirty one residents at varying levels of training participated. After the training session, there was a significant improvement noted in mean scores for comfort level with LOA (6.3 versus 7.7, 𝑃=.007), comfort level with enterotomy repair (2.8 versus 6.4, 𝑃<.0001), understanding principles of LOA (5.0 versus 7.7, 𝑃<.0001), understanding principles of enterotomy repair (3.5 versus 7.0, 𝑃<.0001), and familiarity with instruments used (5.8 versus 7.3, 𝑃=.01). Conclusion. Training sessions using ex-vivo porcine model improve resident perception of knowledge and comfort with LOA and enterotomy repair.